1959
DOI: 10.1039/jr9590003957
|View full text |Cite
|
Sign up to set email alerts
|

796. Steric effects in di- and tri-arylmethanes. Part I. Electronic absorption spectra of o-methyl derivatives of Michler's hydrol blue and crystal violet; conformational isomers of crystal violet

Abstract: The first frequency absorption bands of o-methyl derivatives of Michler's Hydrol Blue and Crystal Violet show the expected reductions in frequency and intensity owing to the enforced rotation of the aryl rings.The conformation of the 2,6-dimethyl derivative of Crystal Violet is discussed, and evidence against the existence of a conformational isomer of Crystal Violet is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…16 The reasons behind this red shift are difficult to ascribe to any one factor, since although a bathochromic shift should be produced by the extension of the chromophoric system provided by the naphthyl ring, 40 a similar shift has also been shown to result from ortho-and meta-crowding of one of the rings of CV. 6, 24 The presence of a single band is usually considered a good indication of the involvement of all terminal amino groups in the resonance system, although PPP-MO calculations, using the parameters determined for Malachite Green (i.e. both dimethylamino groups are equally involved), predict a slight splitting of the two transitions of 2a with a bathochromic shift of the band associated with the naphthyl-phenyl axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The reasons behind this red shift are difficult to ascribe to any one factor, since although a bathochromic shift should be produced by the extension of the chromophoric system provided by the naphthyl ring, 40 a similar shift has also been shown to result from ortho-and meta-crowding of one of the rings of CV. 6, 24 The presence of a single band is usually considered a good indication of the involvement of all terminal amino groups in the resonance system, although PPP-MO calculations, using the parameters determined for Malachite Green (i.e. both dimethylamino groups are equally involved), predict a slight splitting of the two transitions of 2a with a bathochromic shift of the band associated with the naphthyl-phenyl axis.…”
Section: Discussionmentioning
confidence: 99%
“…This solvent system was chosen to allow comparison with earlier work 1 and because its acidity is sufficient to promote the complete formation of the dye cation while minimising the possibility of forming other species such as dications. 24 The use of acetic acid also has the advantage of giving easy access to a wide range of solutions of different acid strengths as the addition of water promotes the ionisation of the acid. The dyes were found to obey Beer's law in the concentration range 1-2.5 × 10 Ϫ5 , a range in which the maximum absorbance was kept between 0.5 and 0.9.…”
Section: Methodsmentioning
confidence: 99%
“…CV + ClO 4 − are not sufficiently soluble in isooctane to permit a direct determination of the absorption coefficient 19 but aggregation among TPMs is a well-established phenomenon in aqueous solution. 2,22 Thus, 10 −3 M solutions of CV + AcO − in water absorb with a maximum at 540 nm, 15 which is a blue-shift from the value 598 nm observed in dilute aqueous solution and an indication of aggregation. Similar observations have been made with the rhodamines.…”
Section: Electronic Absorption Spectra Of (R 2 N) 3 Tota +mentioning
confidence: 96%
“…considering the influence of various solvents, with the aim of understanding decomposition mechanism. [2][3][4][5][6][7][8][9][10][11][12] They demonstrated that decomposition of these dyes takes place by demethylation and, in the presence of oxygen, by oxidation. Previous studies on CV degradation by irradiation with UV light were made by the authors using UV-Vis spectrophotometry, high-performance liquid chromatography-photo diode array detector (HPLC-PDA) and only occasionally by LC-mass chromatography (MS).…”
Section: Introductionmentioning
confidence: 99%